Psychological counseling skills among female counselors in the secondary stage in the locality of Khartoum - Ahmed, Ghada Elameen (Journal of Educational and Psychological Sciences, 2024)
The study aimed to find out the availability of psychological counseling skills among counselors in the Khartoum locality, in addition to knowing the differences in the averages of counseling skills, which are attributed to the variable of specialization, training, and years of experience. The research sample consisted of (24) secondary school counselors during the year 2022/2023, who were selected purposefully. The study followed by a descriptive-analytical approach, and a questionnaire consisting of (52) phrases measuring three dimensions were used: personal, performance, and cognitive skills. The results of the work showed that the level of counseling skills is high by an average of (3.97), and the results indicated that there were no statistically significant differences in the means of counseling skills attributed to the variable of specialization, training, and years of experience, except for the field of personal skills, where the differences in the field of training came in favor of the category (more than 5 courses), as well as differences due to the difference in experience years in the areas of performance and personal skills in favor of the category of experience years (more than 10 years). Based on this survey findings, some recommendations were developed such as benefiting from the skills of the girl guides in the locality of Khartoum and disseminating them to the rest of the localities, focusing on intensive training and refining experiences.